Visual Attention, Driving Behavior and Driving Performance among Young Drivers in Sleep-deprived Condition - Wijayanto, T; Marcilia, S R; Lufityanto, G (KnE Life Sciences, 2018)
Traffic accident is one of the main causes of death among young drivers, both in developed and developing country. Sleep deprivation is agreed to be one of the major contributing factors. In this study, we investigate the effect of sleep deprivation on visual attention during driving and how it contributes to driving behaviors and performance. Twelve male students (mean age = 21.6 years, SD = 0.6 years) who already had valid driving license participated in this study. They were required to drive on a driving simulator in two conditions: normal sleep and sleep-deprived condition. In normal sleep condition, participants were allowed to have a normal sleep for at least 8 h prior to having driving simulation session, whereas in sleep-deprived condition, participants performed simulated driving session after 24 h of continuous sleep deprivation. We found that visual attention, represented by fixation duration and number of fixation on Direct Sight, decreased during driving simulation in sleep deprivation condition. In addition, we observed performance deterioration in sleep deprivation condition. Keywords: sleep deprivation, visual attention, driving behavior, driving performance